Assessment of Lead, Cadmium and Copper concentrations in Raw Milk Collected from different location in Iraq - S. Alani, Marwa; N. Al-Azzawi, Muhammad (Iraqi Journal of Science, 2023)
Raw milk is subjected to various physical, chemical and biological pollutants due to produce, a transporting and marketing processes. The current study was designed to examine raw milk samples which were collected from different locations of Iraq. The highest mean value of Pb content [1.801±0.311 ppm] was recorded while the lowest mean value [0.941±0.104 ppm]. The highest mean value [1.532±0.124 ppm] and gave the lowest mean value [0.063±0.044 ppm] of Cd content. This study has the highest mean value of Cu content was [0.931±0.092 ppm] and but the lowest mean value was [0.308±0.029 ppm]. Metals contents of raw milk in this study showed higher than standards of the International Dairy Federation [IDF].